Are there common human leucocyte antigen associations in juvenile idiopathic arthritis and periodontitis? - Stefan Reichert (Blackwell Synergy, 2007)
Aim: The aim of this study was to evaluate common human leucocyte antigen (HLA) associations in patients with juvenile idiopathic arthritis (N5110), in patients with generalized aggressive periodontitis (N550) and in patients with chronic periodontitis (N5102) in comparison to healthy controls (no periodontitis, no arthritis N5102). Material and methods: HLA-class I and II markers were determined using microlymphocytotoxicity test and polymerase chain reaction with sequence specific primers. Statistical analyses were carried out by w2-test and Yates’ correction. If no5 Fisher’s exact test was performed. In the arthritis group the influence of HLA on attachment loss was determined by using backwards logistic regression considering age, gender, smoking, plaque level, and the duration of the disease. Results: In comparison with the controls HLA-DRB3n occurred more frequently in both females suffering from juvenile idiopathic arthritis (74.58% versus 54.54%, p50.024) and females suffering from chronic periodontitis (73.02% versus 54.54%, p50.035). Furthermore, among patients with juvenile idiopathic arthritis an increased odds ratio (OR) for attachment loss was found in subjects who expressed HLA-An01 (OR54.6, p50.014) or HLA-An01:DRB3n (OR54.3, p50.031). Conclusion: HLA-DRB3n could be a common putative risk indicator for juvenile idiopathic arthritis and chronic periodontitis among females.